Pengaruh Metode Struktural Analitik Sinetik Berbantukan Media Flashcard Terhadap Kemampuan Membaca Permulaan Kelas I SDN Rang Perang Laok - Rika Aprilia; Widya Trio Pangestu (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the effect of the Synthetic Structural Analytical method using flashcard media on the beginning reading ability of class I students at SDN Rang Warga Laok. This research uses quantitative methods with a pre-experimental research design and a one group pretest-posttest model. The sample used in this research was 14 students using saturated sampling techniques. Data collection used student reading ability test instruments and teacher and student activity observation sheets. The results of the research show that 1) The results of the paired sample t-test calculation at a significance level of 0.05 show that the sig (2-tailed) value is 0.001 < 0.05, so it can be concluded that there is an influence of the Synthetic Structural Analytical method using flashcard media. on the initial reading ability of class I students at SDN Rang Warga Laok 2) the application of the Synthetic Structural Analytical method using flashcard media in learning activities that lasted for 3 meetings was carried out well and obtained an average implementation score for the SAS learning method of 100% in the very good category , the average teacher activity score is 98% in the very good category and the average student activity score is 82% in the very good category.